Bull's eye and pigment maculopathy are further retinal manifestations of an abnormal Bruch's membrane in Alport syndrome. (4th May 2017) - Savige, Judy; Wang, Yanyan; Crawford, Andrew; Smith, James; Symons, Andrew; Mack, Heather; Nicholls, Kathy; Wilson, Diane; Colville, Deb
ABSTRACT: Background and Objectives : The retinal features of Alport syndrome include a central and peripheral fleck retinopathy, temporal retinal thinning, and a macular hole. Here we describe further retinal abnormalities. Methods : We identified a case of bull's eye maculopathy 20 years previously in a 68-year-old female, and reviewed archived retinal images from our cohort of X-linked (28 males, 28 females) or autosomal recessive ( n = 13) Alport syndrome. All individuals had Alport syndrome confirmed on genetic testing or renal biopsy, were examined by an ophthalmologist, and underwent retinal imaging (KOWA non-mydriatic camera, Japan). Results : The index case had the p.Q379X variant in COL4A5 and currently had renal impairment, (eGFR = 45 ml/min/1.73 m 2 ), bilateral hearing loss, and central and peripheral retinopathies. Her maculopathy had deteriorated, and she had a bilateral central visual field loss. Optical coherence tomography (Heidelberg Spectralis) demonstrated a disrupted retinal pigment epithelium and retinal atrophy. We identified a further early bull's eye maculopathy (1/69, 1.4%) from a female with autosomal recessive disease and normal renal function. We also noted a subtle pigment maculopathy associated with an abnormal retinal pigment epithelium in 27 (27/69, 39%) subjects with Alport syndrome, in both males (8/28, 29%) and females (13/28, 46%) with X-linked disease, and in autosomal recessive disease (6/13, 38%). Conclusions : The bull's eye and pigment maculopathies in Alport syndrome result mainly from the damaged Bruch's membrane and overlying retinal pigment epithelium. Bull's eye maculopathy affects vision and patients should undergo regular monitoring for retinal complications.